Editorial: action to protect the independence and integrity of global health research - Storeng, Katerini T.; Abimbola, Seye; Balabanova, Dina; McCoy, David; Ridde, Valery; Filippi, Veronique; Roalkvam, Sidsel; Akello, Grace; Parker, Melissa; Palmer, Jennifer; Bozorgmehr, Kayvan (BMJ global health, 2019)
In a recent Viewpoint in the Lancet , some of us shared our experience of censorship in donor-funded evaluation research and warned about a potential trend in which donors and their implementing partners use ethical and methodological arguments to undermine research.1 - - Reactions to the Viewpoint—and lively debate at the 2018 Global Symposium on Health Systems Research —suggest that similar experiences are common in implementation and policy research commissioned by international donors to study and evaluate large-scale, donor-funded health interventions and programmes, which are primarily implemented in low resource settings. ‘We all have the same stories’, was one of the first comments on the Viewpoint, followed by many private messages divulging instances of personal and institutional pressure, intimidation and censorship following attempts to disseminate unwanted findings. Such pressure comes from major donors and from international non-governmental organisations (NGOs) obliged to have an external assessment but who then maintain a high degree of confidentiality and control. - - That such experiences are widespread reflects the deeply political nature of the field of ‘global health’ and the interconnections between priority setting, policy making and project implementation, which sit within a broader set of deeply entrenched power structures.2 3 Researchers in this field routinely find themselves working within—and studying—complex power relations and so experience challenges in negotiating their own position between interests of commissioning agencies and funders, implementers and country governments, as well as those of their own research institutions and their partnerships with other researchers spanning high-income, middle-income and low-income countries.4-7 They often receive research funding from major donor agencies like the UK Department of International Development (DFID), the US Agency for International Development (USAID), the Agence Française de Développement (AFD), UNITAID and the Bill and Melinda Gates Foundation,8 who commission evaluations for their own funded projects, even though they have …
Signatories: [...] Bozorgmehr, Kayvan, Bielefeld University/Heidelberg University Hospital, Germany.[Und weitere]
Gesehen am 10.12.2019